2016
DOI: 10.1155/2016/8491320
|View full text |Cite
|
Sign up to set email alerts
|

Serous Retinal Detachment Associated with Dome-Shaped Macula and Staphyloma Edge in Myopic Patients before and after Treatment with Spironolactone

Abstract: Objective. Serous retinal detachment (SRD) is a common anatomical complication associated with dome-shaped macula (DSM) and staphyloma margin in myopic patients. Here we described the anatomical and functional outcomes obtained with the use of oral spironolactone, a mineralocorticoid antagonist, in the management of myopic patients with SRD associated with DSM and staphyloma margin. Methods. We evaluated both eyes of twelve myopic patients with long-standing SRD associated with DSM or staphyloma margin. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Taking these facts into account, it is difficult to understand validated therapy leading to the resolution of serous retinal detachment related to dome-shaped macula. For example, laser photocoagulation,8 photodynamic therapy,13 15 antivascular endothelial grown factor13 and spironolactone24 therapy have all been tried with inconclusive results. Bearing in mind that spontaneous resolution is possible in this pathology, some researchers have recommended observation without treatment 3 15 25.…”
Section: Discussionmentioning
confidence: 99%
“…Taking these facts into account, it is difficult to understand validated therapy leading to the resolution of serous retinal detachment related to dome-shaped macula. For example, laser photocoagulation,8 photodynamic therapy,13 15 antivascular endothelial grown factor13 and spironolactone24 therapy have all been tried with inconclusive results. Bearing in mind that spontaneous resolution is possible in this pathology, some researchers have recommended observation without treatment 3 15 25.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the presence of SRD in patients presenting with DSM [ 1 , 2 , 6 , 7 , 8 ]. Different hypotheses were advanced to explain SRD appearance.…”
Section: Discussionmentioning
confidence: 99%
“…А. Sanz et al также продемонстрировали эффек-тивность данного препарата: в дозе 50 мг в тече-ние 6 мес. на 14 глазах 12 пациентов [28]. P. Rocha Cabrera et al, в свою очередь, показали эффек-тивность данного вида лечения [27].…”
Section: методы леченияunclassified